Human brucellosis in Turkey: different clinical presentations - Guler, Selma; Kokoglu, Omer Faruk; Ucmak, Hasan; Gul, Mustafa; Ozden, Sevinc; Ozkan, Fuat (The Journal of Infection in Developing Countries, 2014)
Introduction: Brucellosis is still endemic in Turkey and presents a major public health risk. The aim of this study wasto investigate the clinical and laboratory properties and complications of brucellosis cases. Methodology: The files of 370 patients (162 males, 208 females) with brucellosis between March 2006 and January 2012 were analyzed retrospectively. Results: The mean age of patients was 39, 6±18.2 years. The major risk factor was unpasteurized dairy products in 155 (41.8%) cases. The complications included hematological (58.1%), osteoarticular (48.3%), hepatobiliary (26.7%), gastrointestinal (10%), and genitourinary system involvement (4.8%). The most frequently seen symptoms were weakness (64.3%), fever (63.2%), sweating (62.7%), arthralgia (59.1%), and lack of appetite (47.8%). A total of 261 patients (70.5%) were acute, 73 patients (19.7%) were subacute, and 36 patients (9.7%) were chronic. In the laboratory tests, AST, ALT and CRP levels were found as elevated in 27.6%, 21.6%, and 69.6% of the patients, respectively. On complete blood count analysis, leukopenia (21.4%), thrombocytopenia (23%), and anemia (70%) were determined. Pancytopenia was more common in acute cases (p = 0.019). Osteoarticular complications increased significantly with increased age (p = 0.005). Conclusions: Brucellosis is a common disease that may be accompanied by serious complications. In endemic regions of brucellosis, people should be taught to avoid unpasteurized dairy products. Clinicians must be aware of multiple system involvement in brucellosis, especially hematological and musculoskeletal systems. Hematological abnormalities occurring during the course of the disease may be misdiagnosed as hematological malignancies.